2019
DOI: 10.18009/jcer.576978
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Context-Based Learning Approach on Prospective Teachers' Understanding of Nanotechnology

Abstract: The aim of this study was to determine the effect of context-based learning approach on science and chemistry prospective teachers' understanding of nanotechnology. The study was carried out with prospective teachers of 4th grade science (21) and 4th grade chemistry (10). A quasi-experimental method was used in this study. As data collection tools, ‚Nanotechnology Test‛ and questionnaire were used. It is revealed that science and chemistry prospective teachers have equal prior knowledge about nanotechnology. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
2
0
3
Order By: Relevance
“…When the studies in the field are examined, the studies on the teaching of context-based teaching practices to pre-service teachers are quite limited. In addition, studies have been found in which the training given to pre-service teachers was done with context-based teaching (Demircioğlu & Özdemir, 2019;Ültay & Usta, 2016). Ültay et al (2018) discussed the comparison of primary teachers' lesson plans in accordance with the REACT and 5E Model.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…When the studies in the field are examined, the studies on the teaching of context-based teaching practices to pre-service teachers are quite limited. In addition, studies have been found in which the training given to pre-service teachers was done with context-based teaching (Demircioğlu & Özdemir, 2019;Ültay & Usta, 2016). Ültay et al (2018) discussed the comparison of primary teachers' lesson plans in accordance with the REACT and 5E Model.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Na literatura, são mencionadas oportunidades como o baixo custo da nanotecnologia, aumento da qualidade de vida e maiores possibilidades de produção. (28)(29)(30) Alpat et al (2017), Sahin e Ekli (2013) realizaram estudos para conscientizar alunos do ensino fundamental e médio sobre a nanotecnologia; seus achados corroboram nossos resultados, como economia de tempo e aumento da qualidade de vida. (31,32) A percepção de risco da nanotecnologia é limitada, mas está crescendo rapidamente.…”
Section: Discussionunclassified
“…By this way, more substantial teaching environments can be created through the contexts in which students can actively take part (Demircioğlu et. al., 2009;Balaban & Özdemir, 2019). Further, if the introduction and use of contexts is accompanied with a lot of care for bridging the meanings of concepts in a daily life context with those in a chemistry context, the students have an opportunity for grasping the relevance of chemistry/science to their lives (De Jong, 2008).…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%